Embracing the Radical Cartographies of the Doggy Dérive : A Walk in Three Acts - O'Brien, Darren (Humanimalia, 2024)
Operating at the intersection of fine art walking practice, psychogeography, and critical animal studies, the practice of Deep Canine Topography seeks to reframe the humble act of the walk-ies as a co-authored, multi-species act of making and performing together. This essay offers a snapshot of my current research, drawing on Erin Manning’s concept of relational movement, Andrew Goodman’s gathering ecologies, Tim Ingold’s meshwork, Deleuze and Guattari’s twin concepts of becoming animal and nomadic subjectivity, as developed by Rosi Braidotti and Dorota Golanska, and Roberto Marchesini’s theories of the Creative Animal. In doing so I consider the potential of the ubiquitous dog walk as an act of creative co-becoming.